Total phenolic content and antioxidant and anticholinesterase activities of medicinal plants from the State’s Cocó Park (Fortaleza-CE, Brazil) (Research, Society and Development, 2021)
The State’s Cocó Park in the city of Fortaleza-CE present mainly a mangrove flora and include landscape and medicinal plants. The aim of this study is determining the total phenol content, antioxidant activity against the free radical DPPH and the inhibition of the enzyme acetylcholinesterase (AChE) in ethanolic extracts of 30 medicinal plants and thus assess which plants have potential against Alzheimer's Disease.  The plants rich in phenolic compounds with amounts ranging from 297.46 ± 26.94 to 599.30 ± 17.08 mg GAE/g plant extract, which showed greater antioxidant activities (with IC50 against DPPH radical from 3.44 ± 0.16 to 3.73 ± 0.12 µg mL-1) and higher acetylcholinesterase inhibiting power (IC50 < 20 μg mL-1) were Anacardium occidentale, Ceiba pentandraLaguncularia racemosa, Mangifera indica, Myracrodrum urundeuva and Terminalia catappa. Then, these species and their constituents are recommended for more specific studies related to Alzheimer´s Disease.